Neuromagnetic brain activities associated with perceptual categorization and sound-content incongruency: a comparison between monosyllabic words and pitch names - Tsai, Chen-Gia; Chen, Chien-Chung; Wen, Ya-Chien; Chou, Tai-Li (Frontiers in Human Neuroscience, 2015)
In human cultures, the perceptual categorization of musical pitches relies on pitch-naming systems. A sung pitch name concurrently holds the information of fundamental frequency and pitch name. These two aspects may be either congruent or incongruent with regard to pitch categorization. The present study aimed to compare the neuromagnetic responses to musical and verbal stimuli for congruency judgments, for example a congruent pair for the pitch C4 sung with the pitch name do in a C-major context (the pitch-semantic task) or for the meaning of a word to match the speaker’s identity (the voice-semantic task). Both the behavioral data and neuromagnetic data showed that congruency detection of the speaker’s identity and word meaning was slower than that of the pitch and pitch name. Congruency effects of musical stimuli revealed that pitch categorization and semantic processing of pitch information were associated with P2m and N400m, respectively. For verbal stimuli, P2m and N400m did not show any congruency effect. In both the pitch-semantic task and the voice-semantic task, we found that incongruent stimuli evoked stronger slow waves with the latency of 500-600 ms than congruent stimuli. These findings shed new light on the neural mechanisms underlying pitch-naming processes.